Meta Analisis Pengaruh Model Discovery Learning dan Problem Based Learning terhadap Kemampuan Berfikir Kritis Peserta didik Kelas V SD - Eskris, Yosiana (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine the effect of the Discovery Learning and Problem Based Learning on the critical thinking skills of fifth grade elementary school students. The first step is to formulate hypotheses, collect data, test hypotheses and formulate conclusions. The research method uses meta-analysis by summarizing the results of various research studies from electronic journals regarding the influence of the modelDiscovery Learning and Problem Based Learning published in national journals. data collection by browsing electronic journals throughgoogle scholar and google scores. In processing the data using Meta Analysis, namely by describing the data. The results of the search obtained 10 national journals. The results of the analysis show that the Problem Based Learning learning model is able to improve students’ critical thinking starting from the lowest score of 2.70% and the highest score of 48.00% with an average of 16, 32%. For the Discovery Learning the increase in students’ critical thinking starts from the lowest 2.5% and the highest 35.31% with an average of 12.03%. This shows that the modelProblem Based Learning more influential than the model Discovery Learning in improving the critical thinking of fifth grade elementary school students.